Pengaruh Budaya Organisasi Dan Komunikasi Terhadap Kinerja Karyawan Pada PT Pos Indonesia (Persero) Kantor Pusat Kota Tangerang Selatan - Tumanggor, Rahmayanti (LAP4B, 2024)
This study aims to determine whether there is a positive and significant influence between Organizational Culture and Communication either partially or simultaneously on employee performance at PT Pos Indonesia Persero South Tangerang City. There is an influence of Organizational Culture and Communication on employee performance at PT Pos Indonesia (Persero) South Tangerang Head Office. Proven by the regression equation Y = 5.750 + 0.554 X1 + 0.306 X2, the correlation coefficient (R) value of 0.718 which means that the coefficient between the Organizational Culture and Communication variables on Employee Performance is strong, the known coefficient of determination (KD) = (R2) x 100% obtained from R, namely KD = 0.516 x 100% = 51.6% while the remaining 38.4% (100%-51.6%) is the influence of other factors not examined, the output is known Fhitung of 68.662 and a significance value of 0 while the value is 3. 7 So it can be concluded that Fhitung> Ftabel (68.662> 3.07) and significance <0.05 (0 <0.05), then Ha is accepted, so it can be concluded that Organizational Culture and Communication together have an effect on Employee Performance.